Digital financial inclusion and residents' health: evidence from rural China - Lin Tian; Weijian Han; Weilun Tian (Springer, 2024)
Abstract The growth of digital financial inclusion has provided new ways of providing financial services in rural areas, greatly affecting the quality of life and health of rural residents. Using data from the China Household Finance Survey, we examine how digital financial inclusion (DFI) impacts the health of rural residents. The results show that DFI can enhance residents' health. Notably, DFI positively impacts the health of rural residents by promoting commercial insurance, improving medical conditions, and enhancing agricultural production efficiency. Additionally, DFI has a more significant effect on improving the health of low-income residents and those in less-developed areas. This research provides compelling evidence to substantiate the assertion that DFI contributes to enhancing the health of rural residents. It offers empirical support and a basis for decision-making to realize the health benefits of digital financial inclusion.